Performance testing of steam ejector air conditioning system - Yap, Fang Yu. (2010)
Low temperature heat energy is the energy generated by heat with temperature between 80–150°C, It is easily available from sources such as automobiles, industrial processes, geothermal and solar energies, etc. One way to reuse the waste heat energy is to convert them into cooling by means of either mechanical compressor-based cooling or non-mechanical cooling systems. With increased concern for global warming and environmental damage, there has been heated interest in this field. Steam ejector refrigeration system makes use of low grade thermal energy or waste heat to generate cooling. These systems have several advantages over the conventional vapor compression system. These include no moving parts (except the pump) and hence no lubrication required, very little wear and potentially a very reliable system. In addition, these systems are heat powered. Therefore, waste heat, solar heat, biomass or geothermal energy can be utilised via these systems. One major disadvantage of it is its low COP value of 0.2-0.5. Therefore it is rarely used as an independent cycle.